ORGANIZATION OF TRAINING ON STUDYING METHODS AND MEANS OF DISTANCE LEARNING FOR UNIVERSITY TEACHERS - Bolilyi В.О.; Matiash В.В.; Riezina О.В. (Journal of Information Technologies in Education (ITE), 2020)
The paper describes a model of implementing teacher professional advancement courses in the form of training on learning methods and means of distancelearning in the Central Ukrainian State Pedagogical University. The preparation for training included the analysis of researches of native and foreign authors that concern the issue of organizing distancelearning, shaping teachers’ competences, creating programs for teaching adults, implementing principles of interactive learning, forming personal educational environment. The paper highlights the problems that appeared when the first attempts to introduce distancelearning at the university failed, the ways of solving these challenges are defined. In particular, it was suggested to invite those instructors as coaches who were the coaches in the Intel course “Training for the Future” and had the experience of teaching adults. The complete set of regulatory documents as well as the complex of teachingmaterials for the training were prepared and approved in advance. The participants of the first training were carefully selected (they were to have a high level of motivation). The result of a three-month preparation period was the first successful training “Developing distancecourses by means of Wiki-CDPU, Cloud-CDPU and Moodle-CDPU in January 2015 that comprised 108 hours and 10working days (10 modules). The participants developed two distanceelectronic courses in the process of training. One course uses themeans of Wiki-CDPU and Cloud-CDPU, the other one –the means of Moodle-CDPU. The paper describes the training objectives and the teaching content that includes theoretical and practical aspects; each content module contains lessons’ themes and the number of hours for studying them. The paper proves that the components of the information infrastructure formed in the Central Ukrainian State Pedagogical University (Wiki-site, cloud storage and the Moodle system of learning management, in particular) are effective tools of organizing distancelearning. Nine training sessions were conducted using the scheme described, with two groups in each training session. The total percentage of participants who successfully completed 85% of tasks and got the certificate is 99%. The provision of educational process with electronic teaching courses at the university increased from 12% in 2014 to 89% in 2017.